The Fortifications of Hull between 1321 and 1864. Issue 1 (2nd January 2018) - Evans, D.H.
Abstract : As one of the most important ports on the east coast of England, Hull had a major strategic role as a supply base for English armies, particularly in their campaigns against Scotland. Consequently, its defence was a major consideration for the English Crown. The medieval and later town defences of Hull were amongst the strongest in Yorkshire. From 1321-4 until 1776 the town was surrounded on three sides by a substantial Town Ditch and bank, later fronted by a circuit of brick walls incorporating numerous gates and towers; the fourth side, opening onto the River Hull and the town's waterfronts, was protected by a boom chain slung across the entrance to the river. This paper summarizes the historical and archaeological evidence not only for the defences on the west bank of the River Hull, surrounding the Old Town, but also the better-known Henrician and Stuart military defences on the east bank of the river.